Assessment of technology transfer office performance for value creation in higher education institutions - Stankevičienė, Jelena; Kraujalienė, Lidija; Vaiciukevičiūtė, Agnė (Journal of Business Economics and Management, 2017)
Innovative activities, knowledge exchange, patenting and commercialization of know-how are crucial to the value creation process in higher education institutions and other research organizations. The article analyses the technology transfer performance indicators of value creation. The methodology to identify and assess the technology transfer activities with the highest impact on created value are proposed in the paper. The following research methods were invoked: FARE method, allowed to calculate weights of each technology transfer performance indicator, when TOPSIS method redress all different indicators’ results and rank universities. The application of the proposed methodology was based on empirical data collected from Lithuanian universities. The results of the study reveal the importance of science business partnerships, TTO competence and scientists’ trust of TTO, applying particular technology transfer policy. The obtained results would be beneficial for universities technology transfer policy formation to maximize universities created value.